Competitive Agricultural Technology Funds in Developing Countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Competitive Agricultural Technology Funds in Developing Countries GJ Gill and D Carney. Overseas Development Institute (ODI). 1999. 76 pp. ISBN 0 85003 400 0 £5.95 09.65 Public Affairs Officer, ODI, Portland House, Stag Place, London SW1E 5DP, U